Comorbid anxiety disorders in late-life depression: results of a cohort study. (5th November 2014) - van der Veen, D.C.; van Zelst, W.H.; Schoevers, R.A.; Comijs, H.C.; Oude Voshaar, R.C.
ABSTRACT: Background: Comorbid anxiety disorders are common in late-life depression and negatively impact treatment outcome. This study aimed to examine personality characteristics as well as early and recent life-events as possible determinants of comorbid anxiety disorders in late-life depression, taking previously examined determinants into account. Methods: Using the Composite International Diagnostic Interview (CIDI 2.0), we established comorbid anxiety disorders (social phobia (SP), panic disorder (PD), generalized anxiety disorder (GAD), and agoraphobia (AGO)) in 350 patients (aged ≥60 years) suffering from a major depressive disorder according to DSM-IV-TR criteria within the past six months. Adjusted for age, sex, and level of education, we first examined previously identified determinants of anxious depression: depression severity, suicidality, partner status, loneliness, chronic diseases, and gait speed in multiple logistic regression models. Subsequently, associations were explored with the big five personality characteristics as well as early and recent life-events. First, multiple logistic regression analyses were conducted with the presence of any anxiety disorder (yes/no) as dependent variable, where after analyses were repeated for each anxiety disorder, separately. Results: In our sample, the prevalence rate of comorbid anxiety disorders in late-life depression was 38.6%. Determinants of comorbid anxiety disorders were a lower age, female sex, less education, higher depression severity, early traumatization, neuroticism, extraversion, and conscientiousness. Nonetheless, determinants differed across the specific anxiety disorders and lumping all anxiety disorder together masked some determinants (education, personality). Conclusions: Our findings stress the need to examine determinants of comorbid anxiety disorder for specific anxiety disorders separately, enabling the development of targeted interventions within subgroups of depressed patients.